2020
DOI: 10.33711/yyuefd.691525
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğretmenlerinin Öğretim Programına Bağlılıklarının İncelenmesi

Abstract: ANOVA were used in the data analysis. In case ANOVA test revealed a significant difference, LSD Test was used for pairwise comparisons. As a result of the study, it was seen that the secondary school teachers generally had a high level of curriculum fidelity.When examined on the basis of sub-dimensions, it was determined that the most positive opinions relate with "the quality of the application" and "the reactions of the participants"; the most negative opinions relate with "time" and "teacher education" dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 4 publications
3
8
0
12
Order By: Relevance
“…In our study, the results from the descriptive statistics datasets showed that teachers' curriculum fidelity was very high, indicating that teachers tend to transfer the curriculum into the teaching and learning process as it was originally designed. A thorough review of the relevant literature revealed that previous studies (Aslan and Erden, 2020;Burul, 2018;Tekbıyık and Akdeniz, 2008) reached similar conclusions.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 61%
“…In our study, the results from the descriptive statistics datasets showed that teachers' curriculum fidelity was very high, indicating that teachers tend to transfer the curriculum into the teaching and learning process as it was originally designed. A thorough review of the relevant literature revealed that previous studies (Aslan and Erden, 2020;Burul, 2018;Tekbıyık and Akdeniz, 2008) reached similar conclusions.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 61%
“…It was also found that preservice teachers' curriculum literacy levels were at a high level. Similarly, studies conducted with prospective teachers (Dilek, 2020;Çetinkaya & Tabak,2019;Şahin,2020) and teachers (Aygün,2019;Erdem & Eğmir, 2018;Gündoğan, 2019;Güneş Şinegove Çakmak, 2021, Süral & Dedebali, 2018Aslan & Gürlen, 2019;Kuyubaşıoğlu, 2019;Keskin, 2020;Gülpek, 2020, Yılmaz & Kahramanoğlu, 2021 showed that they had high levels of curriculum literacy levels. However, some studies (Kahramanoğlu, 2019;Yıldız, 2019) reported a moderated level of curriculum literacy.…”
Section: Discussion and Recommendationsmentioning
confidence: 97%
“…In order not to waste the effort, the time and the money spent on the curriculum, it is important to determine to what extent the curriculum has been adopted and put into practice by teachers (Dikbayır & Bumen, 2016). The studies on curriculum fidelity have increased recently both in national and international literature (Arslan-Celik, 2020; Aslan & Erden, 2020;Bas & Senturk, 2019;Bay et al, 2017;Bumen et al, 2014;Burul, 2018;C. Gurbuz, 2020;Can, 2020;Dikbayır & Bumen, 2016;Durlak, 2016;Dusenbury et al, 2003;Johnson, 2019;Kabas, 2020;Karadag-Caydasi, 2019;Karakuyu & Oguz 2021;Mihalic, 2004;Nevenglosky, 2018;Pence et al, 2008;S.…”
Section: Introductionmentioning
confidence: 99%